Use of rapid tests for perinatal HIV infection in resource-limited settings - Moodley, Dhayendre; Moodley, Pravi; Moodley, Jagidesa; Coovadia, Hoosen M.; Esterhuizen, Tonya (Journal of Pediatric Infectious Diseases, 2006)
Early testing strategies such as human immunodeficiency virus (HIV) DNA and RNA assays have become popular, cheaper and reliable, however the measures of success of Prevention of Mother-to-Child Transmission (PMTCT) programs in predominantly breastfeeding populations often depend on long term follow-up and HIV testing of children. Diagnosis in PMTCT programs in resource-poor countries therefore remains dependent on serological assays. The use of rapid HIV tests in perinatal HIV diagnosis, as recommended by the WHO, was based on the sensitivity and specificity of the enzyme-linked immuno-assay (ELISA) in children and not guided by an independent evaluation of rapid tests. For the purpose of ensuring a reliable diagnosis of perinatal HIV infection in predominantly breastfed children and largely resource-poor settings in Sub-Saharan Africa, we evaluated a HIV rapid test against the ELISA in serial plasma samples. We tested stored plasma samples for HIV antibodies, using a rapid test (Abbott Determine HIV1/2, Abbott Diagnostics, Wiesbaden, Germany) from a cohort of children between 12 and 18 months of age, enrolled in the PETRA (perinatal transmission) study at the Durban site, and compared to pre-determined real-time ELISA results. Using the ELISA results at 18 months as gold standard, the sensitivity of the ELISA at 12 and 15 months was 100% (95% CI 79–100), and specificity improved from 90.4% (95% CI 86–94) at 12 months to 99.5% (95% CI 97–100) at 15 months. The sensitivity of the rapid HIV test when compared to ELISA results at 18 months was 100% (95% CI 46–98) at 12 and 15 months, and the specificity was 89% (95% CI 80–94) and 99% (95% CI 92–100) at 12 and 15 months respectively. The negative predictive values for the rapid test at 12, 15 and 18 months were 100% (95% CI 94–100). Using the 18 month ELISA as the gold standard, the rapid test at 12 and 15 months demonstrated similar specificities to the corresponding ELISA tests. We concluded that the sensitivity and specificity of the rapid HIV test remained optimal (100%) for the diagnosis of HIV infection in children at 18 months. The earlier use of a rapid test at 15 months correctly excluded HIV infection in 99% of the children. Any earlier use of rapid tests without subsequent confirmation could result in an estimated 10% or more children misdiagnosed as HIV infected.
Keywords: Perinatal HIV infection; rapid HIV test